Skrining Fitokimia dan Uji Antioksidan Ekstrak Daun Cabai Rawit (Capsicum frutescens L.) - Esti Febri Fatwami; Sri Royani (Journal Syifa Sciences and Clinical Research, 2023)
Chili is a plant that is widely cultivated in indonesia. Chili leaves are knowon to have many health benefits. This has something to do with the content of secondary metabolites in it. This research was conducted to determine the content of secondary metabolites in chili leaves. The method used was in the form of phytochemical screening and antioxidant activity test using the DPPH method. The identification of the phytochemicals carried out included the identification of alkaloids, flavanoids, saponins, triterpenoids, quinones and phenols. The results of the phytochemical screening showed that the compounds contained in cayenne pepper leaf extract that extracted using 96% alcohol were alkaloids, flavonoids, and phenols. While the antioxidant test results on cayyenne pepper leaf extract showed an IC50 value of 78,03 Âµg/ml.